France in search of a new administrative order - Rouban Lac
In recent years, drastic political changes in France have produced notnew questions on the national administrative pattern. The "alternance" did not basically alter public administration weight or social structure. At the same time, as a new institutional game was installed (decentralization, EC integration process, new demands coming from citizens), administrative change ("modernization") gained new interest. A general discussion of this modernization process (civil service management, policy evaluation, etc.) shows that, in many respects, administrative reform is a substitute for political change. The traditional State-centred political system recently gave way to pluralistic policy-centred system. But
Keywords: Public Administration -- France